2017
DOI: 10.3349/ymj.2017.58.4.778
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy of Intravenous Peramivir and Oral Oseltamivir for the Treatment of Influenza: Systematic Review and Meta-Analysis

Abstract: PurposePeramivir is the first intravenously administered neuramidase inhibitor for immediate delivery of an effective single-dose treatment in patients with influenza. However, limited data are available on intravenous (IV) peramivir treatment compared to oral oseltamivir for these patients.Materials and MethodsWith a systematic review and meta-analysis, we compared the efficacy of IV peramivir with oral oseltamivir for treatment of patients with seasonal influenza. MEDLINE, EMBASE, and Cochrane Central Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 17 publications
4
29
0
2
Order By: Relevance
“…Our findings confirm the variability of efficacy of antiviral treatment regimen for severe hospitalized patients with influenza infection. Several SR, including both RCT and observational studies, conducted in the past years have addressed the efficacy and safety of NAI treatment, demonstrating the effectiveness of NAI treatment to reduce severity of influenza in outpatients, and mortality in hospitalized patients, compared without treatment [19][20][21][22][23]. Furthermore, it is widely accepted that the efficacy of NAI treatment is higher if administered within 48 h from symptoms onset [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings confirm the variability of efficacy of antiviral treatment regimen for severe hospitalized patients with influenza infection. Several SR, including both RCT and observational studies, conducted in the past years have addressed the efficacy and safety of NAI treatment, demonstrating the effectiveness of NAI treatment to reduce severity of influenza in outpatients, and mortality in hospitalized patients, compared without treatment [19][20][21][22][23]. Furthermore, it is widely accepted that the efficacy of NAI treatment is higher if administered within 48 h from symptoms onset [5].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, intravenous peramivir therapy might also be considered, but it is only approved for uncomplicated influenza and no consensus has been reached on the appropriate dosing and duration of treatment [5]. A recent SR [19] confronted intravenous peramivir therapy vs oral oseltamivir therapy demonstrating peramivir efficacy in reducing TTCR only in outpatients, with no differences in mortality and length of hospital stay for both in-and outpatients. To date, European guidelines do not include indication for intravenously administered peramivir at dosages different from 600 mg single administration in outpatient settings, while IDSA guidelines suggest to consider administering a multiday dosing regimen, although the optimal regimen is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For patients who cannot tolerate or absorb enteric oseltamivir due to gastric stasis, malabsorption, or other gastrointestinal processes, intravenous peramivir may be an alternative [99,100]; however, studies have not identified an advantage for intravenous peramivir in comparison with enteric oseltamivir [101]. Notably, a randomized trial conducted in three influenza seasons found similar clinical outcomes between IV peramivir and enteric oseltamivir in hospitalized adult influenza patients [102]; a separate trial did not identify significant additional clinical benefit of peramivir in combination with standard-of-care therapy (which often included an NAI) [103].…”
Section: Treatment Of Influenzamentioning
confidence: 99%
“…Once recognizing patients with assumed pLOS, extra works in order to hasten patients' recovery can be put into action: Firstly, selecting a more effective antiviral drug, for example Peramivir. Peramivir can be the choice of antiviral agent in such circumstances, as one study indicated that Peramivir may reduce the time to alleviation of fever [16]; Another study showed lesser adverse events (2.2% to 13.0%) and lesser complications (8.7% to 13.0%) in patients treated with Peramivir, compared with Oseltamivir [17]. Secondly, aggressive patient monitoring, for instance, checking vital signs, input output and laboratory data frequently, may assist in identification of early disease deterioration, and perhaps result in better prognosis [18].…”
Section: Discussionmentioning
confidence: 99%